2021
DOI: 10.1007/s11069-021-05066-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment framework for Mediterranean airports: a focus on extreme temperatures and precipitations and sea level rise

Abstract: The increase of frequency and severity of extreme weather events due to climate change gives evidence of severe challenges faced by infrastructure systems. Among them, the aviation sector is particularly at risk from the potential consequences of climate change. Airports are classified as critical infrastructures because they provide fundamental functions to sustain societies and economic activities. More specifically, Mediterranean airports face risks associated with sea level rise, higher occurrence of extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 34 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…This matrix could aid in identifying the strength and weaknesses of the airport to improve the climate change resilience, in order to support stakeholders in the identification of suitable adaptation strategies. According with [14], specific indicators must be used as proxies for identifying not only hazards, but also exposure and vulnerability characteristics. Those indicators are linked to physical (such as age, percentage of impervious surfaces) and socioeconomic features (e.g., air traffic, number of passengers).…”
Section: Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…This matrix could aid in identifying the strength and weaknesses of the airport to improve the climate change resilience, in order to support stakeholders in the identification of suitable adaptation strategies. According with [14], specific indicators must be used as proxies for identifying not only hazards, but also exposure and vulnerability characteristics. Those indicators are linked to physical (such as age, percentage of impervious surfaces) and socioeconomic features (e.g., air traffic, number of passengers).…”
Section: Model Evaluationmentioning
confidence: 99%
“…They found that the take-off distance required for the medium-sized passenger jet Airbus A 320 increased by an average of 2.7 m/year, while for the smaller de Havilland DHC8-400, it was by 1.4 m/year. In a recent study, De Vivo et al [14] proposed a methodology aimed to define the climate risk level on airports in the Mediterranean region.…”
Section: Introductionmentioning
confidence: 99%
“…The project highlighted that 163 Mediterranean coastal plains are highly prone to marine flooding because of sea level rise for 2100, land subsidence, tsunamis and storms. Many studies are also focused on the assessment of the potential sea level impacts on critical infrastructures, such as ports [44], airports [45,46], and railways (e.g., ongoing study financed by the Italian Ministry of Sustainable Infrastructures and Mobility).…”
Section: Introductionmentioning
confidence: 99%
“…Franchin [93] Cox [33], Serre [94], Johnsen and Veen [90], Bialas [89], and LaLone et al [95] use social indicators, such as decisions of spatial management, Twitter discussion, shelter-seeking populations, etc. De Vivo et al [96] considers the number of green walls and roofs as an indicator to assess the resilience of airports. The application and reliability of all the above indicators should be discussed in future studies for the resilience assessment of TIs.…”
Section: Results Of Indicators' Analysismentioning
confidence: 99%